Shaped by asymmetrical interdependence: a qualitative case study of the external influences on international non-governmental organizations’ implementation of equity principles in HIV/AIDS work - Dyke, Elizabeth; Edwards, Nancy; McDowell, Ian; Muga, Richard; Brown, Stephen (Université d'Ottawa | University of Ottawa, 2014)
Abstract Introduction Addressing inequities is a key role for international non-governmental organizations (INGOs) working in health and development. Yet, putting equity principles into practice can prove challenging. In-depth empirical research examining what influences INGOs’ implementation of equity principles is limited. This study examined the influences on one INGO’s implementation of equity principles in its HIV/AIDS programs. Methods This research employed a case study with nested components (an INGO operating in Kenya, with offices in North America). We used multiple data collection methods, including document reviews, interviews (with staff, partners and clients of the INGO in Kenya), and participant observation (with Kenyan INGO staff). Participant observation was conducted with 10 people over three months. Forty-one interviews were completed, and 127 documents analyzed. Data analysis followed Auerbach and Silverstein’s analytic process (2003), with qualitative coding conducted in multiple stages, using descriptive matrices, visual displays and networks (Miles and Huberman, 1994). Results There was a gap between the INGO’s intent to implement equity principles and actual practice due to multiple influences from various players, including donors and country governments. The INGO was reliant on donor funding and needed permission from the Kenyan government to work in-country. Major influences included donor agendas and funding, donor country policies, and Southern country government priorities and legislation. The INGO privileged particular vulnerable populations (based on its reputation, its history, and the priorities of the Kenyan government and the donors). To balance its equity commitment with the influences from other players, the INGO aligned with the system as well as pushed back incrementally on the donors and the Kenyan government to influence these organizations’ equity agendas. By moving its equity agenda forward incrementally and using its reputational advantage, the INGO avoided potential negative repercussions that might result from pushing too fast or working outside the system. Conclusions The INGO aligned the implementation of equity principles in its HIV/AIDS initiatives by working within a system characterized by asymmetrical interdependence. Influences from the donors and Kenyan government contributed to an implementation gap between what the INGO intended to accomplish in implementing equity principles in HIV/AIDS work and actual practice.